Electrode plate as well as preparation method and application thereof

By using carbonized polymer precursors in lithium/sodium sulfide batteries to build a carbon conductive network, the problems of poor conductivity and poor reaction kinetics are solved, the battery performance is improved and commercialized, and high-power charging and discharge are met need.

CN119153689APending Publication Date: 2024-12-17SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310711292.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The poor conductivity and poor reaction kinetics of existing lithium/sodium sulfide batteries lead to problems such as long charging time and difficulty in charging. The adhesives of traditional electrode sheets limit the conductivity of the battery, affecting the rate performance and commercialization. develop.

Method used

A continuous carbon conductive network is constructed with a carbonized polymer precursor, combining active substances and conductive agents to form a porous electrode sheet, improving the conductivity and reaction kinetics of the electrode, and ensuring structural stability through high-temperature carbonization treatment.

Benefits of technology

It significantly improves the rate performance and reaction kinetics of the battery, reduces polarization, enhances the utilization rate of active materials, and reduces the formation of dead sulfur. This method is cheap and suitable for positive and negative electrode sheets, promoting lithium/sodium dioxin Commercial development of secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153689A_ABST
    Figure CN119153689A_ABST
Patent Text Reader

Abstract

The invention provides an electrode pole piece and a preparation method and application thereof.The electrode pole piece comprises a current collector and an active substance layer arranged on the surface of the current collector, the active substance layer comprises a carbon conductive network, a conductive agent and an active substance, and the conductive agent and the active substance are dispersed in the carbon conductive network; the carbon conductive network is obtained by carbonizing a polymer precursor, a continuous carbon network is contained in the electrode pole piece to tightly connect the porous pole piece layer with the current collector, and active substances, conductive carbon black and other particles in the porous pole piece layer are uniformly dispersed in the continuous carbon network structure. And the conductivity of the electrode is greatly improved while the physical contact of the pole piece is not damaged, so that the rate capability and the reaction kinetics of the battery are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials and relates to an electrode plate and a preparation method and application thereof. Background Art

[0002] With the progress of the times, the popularization of new energy vehicles and the substantial increase in energy storage demand brought about by the development of clean energy, the demand for secondary lithium / sodium batteries has skyrocketed. Clean energy such as hydropower generation, solar power generation, and wind power generation cannot generate electricity stably due to weather conditions, which has brought about the demand for low-cost, large-scale energy storage systems. Lithium / sodium sulfide batteries with high energy density and low cost are very suitable for application in the field of large-scale energy storage.

[0003] Due to the poor conductivity and reaction kinetics of lithium and sodium sulfides, they still face many difficulties in the process of commercialization, and it is urgent to develop pole piece technology with excellent conductive network. On the other hand, the development of new energy vehicles has been very rapid in recent years. The rapid development has brought about slow charging and difficult charging. Although lithium / sodium ion batteries with excellent rate performance are generally used in new energy vehicles, further improvement is still needed. In order to solve the user experience problem caused by long charging time, it is necessary to develop a battery system that can meet high-power charging and discharging, which also puts forward requirements for pole pieces with excellent conductivity.

[0004] The electrode plates disclosed in the prior art are generally composed of active materials, conductive agents, and binders, which are combined together by dissolving in organic solvents and performing slurry mixing, coating, evaporation and other steps. Since the active material, conductive agent, and solvent have no adhesion to the current collector, they cannot be made into pole plates for preparing lithium batteries. The binder can bond the particles of the above-mentioned various electrode materials together to form a slurry with adhesion. Therefore, the binder can effectively bond and maintain the physical state of the active material, enhance the electronic contact between the active material and the conductive agent in the electrode and between the active material and the current collector, and play a role in better stabilizing the physical structure of the pole plate. However, the binder itself is generally a high molecular polymer, and its intrinsic electronic conductivity has certain limitations, which will affect the conductivity of the entire electrode, thereby affecting the reaction kinetics of the battery, and has a certain impact on the rate performance, and even increases the polarization phenomenon of charge and discharge, especially in metal sulfide batteries, where lower conversion kinetics will cause more problems. Summary of the invention

[0005] The object of the present invention is to provide an electrode plate and a preparation method and application thereof, wherein the electrode plate contains a continuous carbon network inside to tightly connect the porous electrode plate layer and the current collector, and the particles of active materials and conductive carbon black in the porous electrode plate layer are evenly dispersed in the continuous carbon network structure, while ensuring that the physical contact of the electrode plate is not destroyed, the conductivity of the electrode is greatly improved, thereby enhancing the rate performance and reaction kinetics of the battery.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides an electrode plate, comprising a current collector and an active material layer arranged on the surface of the current collector, wherein the active material layer comprises a carbon conductive network, a conductive agent and an active material, wherein the conductive agent and the active material are dispersed in the carbon conductive network, and the carbon conductive network is obtained by carbonizing a carbonized polymer precursor.

[0008] The electrode plate of the present invention has an electrode structure with an excellent conductive network, which overcomes the problems of poor conductivity caused by the binder in the traditional electrode structure and optimizes its conductive network, thereby improving the reaction kinetics of the entire electrode, reducing polarization, and enhancing rate performance; in lithium / sodium sulfide batteries, this excellent conductive structure can also increase the nucleation sites of sulfur / sulfide, promote its uniform deposition, improve the utilization rate of active materials and reduce the generation of dead sulfur.

[0009] The excellent carbon conductive network in the electrode plate of the present invention is obtained from a carbonized polymer precursor, which includes any one or a combination of at least two of polyvinyl pyrrolidone, polyethyl acetate, polyacrylonitrile, polyacrylate or carboxymethyl cellulose. Compared with traditional polyvinylidene fluoride binders, these polymers can still tightly adhere the active material and the conductive agent to the current collector even after carbonization, without the phenomenon of powdering or falling off, and play the role of binder and conductor at the same time.

[0010] Preferably, based on the mass of the active material layer being 100%, the mass fraction of the carbon conductive network is 0.2-10%, for example, 0.2%, 1%, 5%, 8% or 10%.

[0011] Preferably, based on the mass of the active material layer being 100%, the mass fraction of the active material is 40-99%, for example, 40%, 45%, 60%, 80% or 99%.

[0012] Preferably, based on the mass of the active material layer being 100%, the mass fraction of the conductive agent is 0.3-30%, for example, 0.3%, 1%, 5%, 10%, 20% or 30%.

[0013] Preferably, the diameter of the carbon conductive network is 5 to 300 nm, for example, 5 nm, 10 nm, 50 nm, 80 nm, 100 nm, 200 nm or 300 nm, etc., preferably 50 to 200 nm.

[0014] Preferably, the conductive agent includes any one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes or graphene, or a combination of at least two of them.

[0015] Preferably, the active material includes a positive electrode active material or a negative electrode active material.

[0016] Preferably, the positive electrode active material includes any one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, sodium nickel iron manganese oxide, sodium iron sulfate, lithium sulfide or sodium sulfide, or a combination of at least two thereof.

[0017] Preferably, the negative electrode active material includes any one of hard carbon, soft carbon, graphite, silicon carbon or silicon monoxide, or a combination of at least two thereof.

[0018] Preferably, the current collector comprises any one of aluminum foil, carbon-coated aluminum foil, copper foil, nickel foam or titanium foil, or a combination of at least two thereof.

[0019] Preferably, the carbonized polymer precursor includes any one of polyvinyl pyrrolidone, polyethyl acetate, polyacrylonitrile, polyacrylate or carboxymethyl cellulose, or a combination of at least two thereof.

[0020] In a second aspect, the present invention provides a method for preparing the electrode sheet according to the first aspect, the preparation method comprising the following steps:

[0021] (1) mixing a carbonized polymer precursor with a solvent to obtain a solution, mixing and grinding an active material and a conductive agent, and then mixing the mixture with the solution to obtain a slurry;

[0022] (2) The slurry is coated on the surface of the current collector and subjected to high-temperature carbonization treatment to obtain the electrode plate.

[0023] The present invention carbonizes the carbonized polymer precursor to construct a pole piece structure with an excellent conductive network. While ensuring that the physical contact of the pole piece is not destroyed, the conductivity of the electrode is greatly improved, thereby enhancing the rate performance and reaction kinetics of the battery. The method is low-cost and can be used in both positive and negative pole pieces, meeting the needs of different lithium / sodium secondary battery systems, and providing a new design idea for the commercial development of lithium / sodium secondary batteries.

[0024] Preferably, the solvent in step (1) comprises N-methylpyrrolidone.

[0025] Preferably, the high-temperature carbonization treatment in step (2) includes pre-carbonization and high-temperature calcination.

[0026] Preferably, the atmosphere of the high temperature carbonization treatment includes nitrogen and / or argon.

[0027] Preferably, the pre-carbonization temperature is 150-250°C, for example, 150°C, 180°C, 200°C, 220°C or 250°C.

[0028] Preferably, the high temperature calcination temperature is 300-600°C, for example, 300°C, 350°C, 400°C, 500°C or 600°C.

[0029] In a third aspect, the present invention provides a battery, comprising the electrode plate as described in the first aspect.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The present invention designs a new type of electrode structure and carbonizes the polymer precursor to construct a pole piece structure with an excellent conductive network. While ensuring that the physical contact of the pole piece is not destroyed, the conductivity of the electrode is greatly improved, thereby enhancing the rate performance and reaction kinetics of the battery. The method is low-cost and can be used in both positive and negative pole pieces, meeting the needs of different lithium / sodium secondary battery systems, and providing a new design idea for the commercial development of lithium / sodium secondary batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a schematic diagram of the structure of the pole piece provided in Example 1 of the present invention, 1-current collector, 2-active material layer, 3-active material, 4-conductive agent, 5-carbon conductive network.

[0033] Figure 2 This is an optical picture of the pole piece provided in Example 3 of the present invention.

[0034] Figure 3 This is an optical picture of the pole piece after cycling provided by Example 3 of the present invention. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0036] Example 1

[0037] This embodiment provides a positive electrode sheet, and the preparation method of the positive electrode sheet is as follows:

[0038] (1) lithium iron phosphate, acetylene black (AB), and polyacrylonitrile (PAN) in a mass ratio of 8:1:1 are taken, PAN is first dissolved in an appropriate amount of N-methylpyrrolidone (NMP) to form a glue solution, and then the lithium iron phosphate and AB are uniformly mixed and ground, and then the glue solution is added and stirred, and a slurry is obtained after the dissolution and stirring are completed;

[0039] (2) The slurry is uniformly coated on aluminum foil, dried and cut to obtain the initial lithium iron phosphate pole piece, which is placed in a muffle furnace and maintained at 200°C for 12 hours, and then placed in a tube furnace, heated to 500°C and calcined for 2 hours under the condition of passing Ar gas, with a heating rate of 5°C / min, and taken out after cooling to obtain the positive electrode pole piece, in which the mass fraction of the carbon conductive network is 6%, the mass fraction of the active material is 83%, and the mass fraction of the conductive agent is 11%. The structural schematic diagram of the pole piece is as follows Figure 1 shown.

[0040] Based on the electrode, a lithium iron phosphate half-cell is made. The electrolyte uses 1M LiTFSI dissolved in EC / DEC / DMC=1:1:1, and the diaphragm uses a polyolefin diaphragm. The specific capacity of the battery at 1C can reach 150mAh / g, and the capacity retention rate is 95% after 200 cycles at 1C. The average coulombic efficiency reaches 99.3%.

[0041] Example 2

[0042] This embodiment provides a positive electrode sheet, and the preparation method of the positive electrode sheet is as follows:

[0043] (1) Lithium sulfide, Ketjen black (KB), and polyvinyl pyrrolidone (PVP) are prepared in a mass ratio of 7:1.5:1.5 under an inert atmosphere. PVP is first dissolved in an appropriate amount of N-methylpyrrolidone (NMP) to form a glue solution, and then lithium sulfide and KB are uniformly mixed and ground, and then added to the glue solution and stirred, and a slurry is obtained after the dissolution and stirring are completed;

[0044] (2) The slurry is uniformly coated on a carbon-coated aluminum foil, and the initial lithium sulfide electrode is obtained after drying and cutting. The initial lithium sulfide electrode is placed in a tubular furnace, heated to 200°C for 12 hours under the condition of passing Ar gas, and then heated to 500°C and calcined for 2 hours at a heating rate of 5°C / min. After cooling, the prepared lithium sulfide electrode with excellent conductive carbon structure is obtained, wherein the mass fraction of the carbon conductive network in the electrode is 10%, the mass fraction of the active material is 75%, and the mass fraction of the conductive agent is 15%.

[0045] Based on the electrode, a lithium sulfide-to-lithium half-cell is made. The electrolyte uses 1M LiTFSI dissolved in DOL / DME=1:1 (3wt% LiNO3 is added), and the diaphragm uses a polyolefin diaphragm. The battery has a specific capacity of 860mAh / g at 0.2C, a remaining capacity of 720mAh / g after 100 cycles, and an average coulombic efficiency of 98%.

[0046] Example 3

[0047] This embodiment provides a positive electrode sheet, and the preparation method of the positive electrode sheet is as follows:

[0048] (1) In an inert atmosphere, sodium sulfide, Ketjen black (KB), and polyvinyl pyrrolidone (PVP) are prepared in a mass ratio of 7:2:1. PVP is first dissolved in an appropriate amount of N-methylpyrrolidone (NMP) to form a glue solution, and then sodium sulfide and KB are uniformly mixed and ground, and then added to the glue solution and stirred until dissolved to obtain a slurry;

[0049] (2) The slurry is uniformly coated on a carbon-coated aluminum foil, and after drying and cutting, an initial sodium sulfide electrode is obtained. The initial sodium sulfide electrode is placed in a tubular furnace, heated to 500°C and calcined for 2 hours under the condition of passing Ar gas, with a heating rate of 5°C / min. After cooling, the prepared sodium sulfide electrode with excellent conductive carbon structure is obtained, wherein the mass fraction of the carbon conductive network in the electrode is 7%, the mass fraction of the active substance is 72%, and the mass fraction of the conductive agent is 21%.

[0050] The optical picture of the pole piece is as follows Figure 2 As shown by Figure 2 It can be seen that the pole piece does not drop material. The optical picture of the pole piece after the cycle is as follows: Figure 3 As shown by Figure 3 It can be seen that there is no material shedding after the pole piece cycle.

[0051] Based on this electrode, a sodium sulfide half-cell is made. The electrolyte uses 1M NaPF6 dissolved in DME, and the diaphragm uses a glass fiber diaphragm. The battery has a specific capacity of 700mAh / g at 0.2C, and the remaining capacity is 500mAh / g after 100 cycles. The average coulombic efficiency reaches 96%.

[0052] Example 4

[0053] This embodiment provides a positive electrode sheet, and the preparation method of the positive electrode sheet is as follows:

[0054] (1) Take anhydrous lithium sulfate (Li2SO4), Ketjen black (KB), and polyvinyl pyrrolidone (PVP) in a mass ratio of 6.5:2.5:1. First, dissolve PVP in an appropriate amount of N-methylpyrrolidone (NMP) to form a glue solution, then evenly mix and grind anhydrous lithium sulfate and KB, add the glue solution and stir, and obtain a slurry after dissolution and stirring;

[0055] (2) The slurry is uniformly coated on a copper foil, and after drying and cutting, an initial lithium sulfate electrode is obtained. The initial lithium sulfate electrode is placed in a tubular furnace, first heated to 180°C and maintained for 12 hours, and then heated to 600°C and calcined for 2 hours under the condition of passing Ar gas at a heating rate of 5°C / min. After cooling, the prepared lithium sulfide electrode with an excellent conductive carbon structure is obtained, wherein the mass fraction of the carbon conductive network in the electrode is 5%, the mass fraction of the active material is 65%, and the mass fraction of the conductive agent is 30%.

[0056] Based on this electrode, a lithium sulfide sodium half-cell is made. The electrolyte uses 1M NaPF6 dissolved in DME, and the diaphragm uses a glass fiber diaphragm. The battery has a specific capacity of 800mAh / g at 0.2C, and the remaining capacity is 600mAh / g after 100 cycles. The average coulombic efficiency reaches 97%.

[0057] Example 5

[0058] This embodiment provides a negative electrode sheet, and the preparation method of the negative electrode sheet is as follows:

[0059] (1) Take hard carbon, Super P (SP), and carboxymethyl cellulose (CMC) in a mass ratio of 8:1:1. First, dissolve CMC in an appropriate amount of N-methylpyrrolidone (NMP) to form a glue solution, then evenly mix and grind the hard carbon and SP, add the glue solution and stir, and obtain a slurry after the dissolution and stirring are completed;

[0060] (2) The slurry is uniformly coated on the carbon-coated aluminum foil, and the initial hard carbon electrode is obtained after drying and cutting. The initial hard carbon electrode is placed in a tubular furnace, and under the condition of passing Ar gas, it is first heated to 180°C and maintained for 12 hours, and then heated to 500°C and calcined for 2 hours, with a heating rate of 5°C / min. After cooling, the hard carbon electrode with excellent conductive carbon structure is obtained. The mass fraction of the carbon conductive network in the electrode is 5%, the mass fraction of the active material is 83%, and the mass fraction of the conductive agent is 12%.

[0061] The hard carbon electrode is used as the negative electrode, and the electrode prepared in Example 4 is used as the positive electrode. A lithium sulfide-to-hard carbon full battery is equipped. The electrolyte uses 1M NaPF6 dissolved in DME, and the diaphragm uses a glass fiber diaphragm. The battery has a specific capacity of 320mAh / g at 0.2C, a remaining capacity of 300mAh / g after 100 cycles, and an average coulombic efficiency of 98%.

[0062] Example 6

[0063] This embodiment provides a negative electrode sheet, and the preparation method of the negative electrode sheet is as follows:

[0064] (1) Take silicon oxide, Super P (SP), and carboxymethyl cellulose (CMC) in a mass ratio of 8:1:1. First, dissolve CMC in an appropriate amount of N-methylpyrrolidone (NMP) to form a glue solution, then evenly mix silicon oxide and SP, grind them, add the glue solution and stir, and obtain a slurry after dissolution and stirring;

[0065] (2) The slurry is uniformly coated on a carbon-coated aluminum foil, and then dried and cut to obtain an initial silicon oxide pole piece. The initial silicon oxide pole piece is placed in a tube furnace, first heated to 180°C and maintained for 12 hours, and then heated to 400°C and calcined for 2 hours under the condition of passing Ar gas, with a heating rate of 5°C / min. After cooling, the pole piece is taken out to obtain the prepared silicon oxide pole piece with excellent conductive carbon structure, wherein the mass fraction of the carbon conductive network in the pole piece is 6%, the mass fraction of the active substance is 82%, and the mass fraction of the conductive agent is 12%.

[0066] The silicon dioxide pole piece is used as the negative electrode, and the pole piece prepared in Example 1 is used as the positive electrode, and a lithium iron phosphate-silicon dioxide full battery is equipped. The electrolyte uses 1M LiTFSI dissolved in EC / DEC / DMC=1:1:1, and the diaphragm uses a polyolefin diaphragm. The specific capacity of the battery can reach 140mAh / g at 1C, and the specific capacity is 130mAh / g after 200 cycles at 1C, and the average coulombic efficiency reaches 99%.

[0067] Example 7

[0068] The only difference between this embodiment and embodiment 2 is that the calcination temperature is 200° C., and the other conditions and parameters are exactly the same as those in embodiment 2.

[0069] Based on the electrode, a lithium sulfide-to-lithium half-cell was made. The electrolyte used was 1M LiTFSI dissolved in DOL / DME=1:1 (3wt% LiNO3 was added), and the diaphragm used was a polyolefin diaphragm. The battery had a specific capacity of 800mAh / g at 0.2C, a capacity of 200mAh / g after 100 cycles at 0.2C, and an average coulombic efficiency of 89%.

[0070] Example 8

[0071] The only difference between this embodiment and embodiment 2 is that no pre-carbonization treatment is performed, and other conditions and parameters are exactly the same as those in embodiment 2.

[0072] A lithium sulfide-to-lithium half-cell was made based on the electrode. The electrolyte used was 1M LiTFSI dissolved in DOL / DME=1:1 (3wt% LiNO3 was added), and the diaphragm used was a polyolefin diaphragm. The battery had a specific capacity of 890mAh / g at 0.2C, a capacity of 110mAh / g after 100 cycles at 0.2C, and an average coulombic efficiency of 87%.

[0073] Comparative Example 1

[0074] The only difference between this comparative example and Example 2 is that polyvinylpyrrolidone (PVP) is replaced by PVDF, and the other conditions and parameters are exactly the same as those in Example 2.

[0075] Comparative Example 2

[0076] The only difference between this comparative example and Example 2 is that polyvinyl pyrrolidone (PVP) is replaced by PVDF and carbonization is not performed (ie, conventional electrode). Other conditions and parameters are exactly the same as those in Example 2.

[0077] It can be seen from Examples 1-6 that the electrode plate of the present invention, whether it is a positive electrode or a negative electrode, can exhibit good coulombic efficiency and cycle performance.

[0078] By comparing Example 2 and Example 7, it can be seen that during the preparation process of the electrode plate of the present invention, the temperature of high-temperature calcination will affect its performance. When the temperature of high-temperature calcination is controlled at 300-600°C, the adhesion performance of the electrode plate is better. If the calcination temperature is too low, the polymer cannot be effectively carbonized, which affects the electronic conductivity inside the plate, and the rate performance and cycle performance of the battery are poor. If the calcination temperature is too high, the performance is not significantly improved and the preparation cost is greatly increased.

[0079] From the comparison between Example 2 and Example 8, it can be seen that the present invention performs a pre-carbonization treatment on the pole piece before high-temperature calcination, which can form a carbon conductive network in situ on the surface of the active material, which is beneficial for the battery to maintain good cycle stability.

[0080] From the comparison between Example 2 and Comparative Example 1, it can be seen that the selection of the carbonized polymer precursor of the present invention is very important. The PVDF binder no longer has an adhesion effect after carbonization, and the active material falls off from the current collector.

[0081] By comparing Example 2 and Comparative Example 2, it can be seen that compared with conventional electrodes, the electrode plate prepared by the present invention has better electronic conductivity, thereby ensuring a good electron transmission path around the lithium sulfide particles, which is beneficial to the capacity and improving the cycle stability of the plate.

[0082] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. An electrode plate, characterized in that: The electrode plate includes a current collector and an active material layer arranged on the surface of the current collector, the active material layer includes a carbon conductive network, a conductive agent and an active material, the conductive agent and the active material are dispersed in the carbon conductive network, and the carbon conductive network is obtained by carbonizing a carbonized polymer precursor.

2. The electrode plate according to claim 1, characterized in that: Based on the mass of the active material layer being 100%, the mass fraction of the carbon conductive network is 0.2 to 10%; Preferably, based on the mass of the active material layer being 100%, the mass fraction of the active material is 40 to 99%; Preferably, based on 100% of the mass of the active material layer, the mass fraction of the conductive agent is 0.3-30%.

3. The electrode plate according to claim 1 or 2, characterized in that: The diameter of the carbon conductive network is 5 to 300 nm, preferably 50 to 200 nm.

4. The electrode plate according to any one of claims 1 to 3, characterized in that: The conductive agent includes any one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes or graphene, or a combination of at least two thereof; Preferably, the active material includes a positive electrode active material or a negative electrode active material; Preferably, the positive electrode active material includes any one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, sodium nickel iron manganese oxide, sodium iron sulfate, lithium sulfide or sodium sulfide, or a combination of at least two thereof; Preferably, the negative electrode active material includes any one of hard carbon, soft carbon, graphite, silicon carbon or silicon dioxide, or a combination of at least two thereof; Preferably, the current collector comprises any one of aluminum foil, carbon-coated aluminum foil, copper foil, nickel foam or titanium foil, or a combination of at least two thereof.

5. The electrode plate according to any one of claims 1 to 4, characterized in that: The carbonized polymer precursor includes any one of polyvinyl pyrrolidone, polyethyl acetate, polyacrylonitrile, polyacrylate or carboxymethyl cellulose, or a combination of at least two thereof.

6. A method for preparing an electrode sheet according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) mixing a carbonized polymer precursor with a solvent to obtain a solution, mixing and grinding an active material and a conductive agent, and then mixing the mixture with the solution to obtain a slurry; (2) The slurry is coated on the surface of the current collector and subjected to high-temperature carbonization treatment to obtain the electrode plate.

7. The preparation method according to claim 6, characterized in that: The solvent in step (1) includes N-methylpyrrolidone.

8. The preparation method according to claim 6 or 7, characterized in that: The high temperature carbonization treatment in step (2) includes pre-carbonization and high temperature calcination; Preferably, the atmosphere of the high temperature carbonization treatment includes nitrogen and / or argon.

9. The preparation method according to claim 8, characterized in that: The pre-carbonization temperature is 150-250°C; Preferably, the high temperature calcination temperature is 300-600°C.

10. A battery, characterized in that: The battery comprises the electrode sheet as described in any one of claims 1 to 5.